2003
DOI: 10.1590/s1516-14392003000200023
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of titanium by plasma nitriding

Abstract: A systematic investigation was undertaken on commercially pure titanium submitted to plasma nitriding. Thirteen different sets of operational parameters (nitriding time, sample temperature and plasma atmosphere) were used. Surface analyses were performed using X-ray diffraction, nuclear reaction and scanning electron microscopy. Wear tests were done with stainless steel Gracey scaler, sonic apparatus and pin-on-disc machine. The obtained results indicate that the tribological performance can be improved for sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
1
21
1
Order By: Relevance
“…The thickness of the fabricated Ti/TiN composite surface layer formed on work piece with groove is quite the same as that of the groove (i.e.~3 mm); this is relatively thicker than those produced using diffusion and re-melting nitriding methods [1,2,[27][28][29][30].…”
Section: Microscopy Of the Fsped Layers Under Nitrogen Gasmentioning
confidence: 85%
“…The thickness of the fabricated Ti/TiN composite surface layer formed on work piece with groove is quite the same as that of the groove (i.e.~3 mm); this is relatively thicker than those produced using diffusion and re-melting nitriding methods [1,2,[27][28][29][30].…”
Section: Microscopy Of the Fsped Layers Under Nitrogen Gasmentioning
confidence: 85%
“…This behavior could be ascribed to the variation of nitrogen content along the nitride layer, which was found to be decreased when moving towards the bulk material [54]. Furthermore, the increase in the friction coefficient is ascribed to the role of the wear debris created during the peel-off of the protective nitride layer, which acts as an abrasive interface between the counter bodies [55][56][57].…”
Section: Wear and Friction Coefficient Measurementsmentioning
confidence: 97%
“…Nevertheless, the TiO 2 film is prone to destruction by the shearing forces acting on implant. This phenomenon can cause separation of the implant from the bone and enhance metal ion release and the formation of wear particles [33] and lowering the wear resistance [20,21].…”
Section: Scanning Electron Micrographs Of Tin and Tialn Coatingmentioning
confidence: 99%
“…It is the most common physical vapor deposition (PVD) hard coating with an excellent combination of performance properties, attractive appearance, and safety (meets FDA requirements for surgical tools and implants as well as food contact applications). Kapczinski et al investigated the usefulness of TiN coating on the pure Ti in terms of tribological behaviour and concluded that the TiN coating improved the tribological ability of dental implants [20]. Rie et al carried out TiN coating on surgical Ti alloys and investigated the effects of TiN coating on the corrosion resistance and biocompatibility [21].…”
Section: Scanning Electron Micrographs Of Tin and Tialn Coatingmentioning
confidence: 99%